Rediseño de una máquina tipo expeller para extracción de aceite de la semilla de sacha inchi con capacidad de 20 kilogramos/hora - Guzmán Brito, Wilson Freddy (2016)
This graduation project entitled "Redesign of machine type expeller for extracting oil from the seeds of Sacha inchi with the capacity of 20 kg/hour", consist in to a redesign a machine capable of extracting the oil from the seed of Sacha inchi, from a machine mill for oil extraction chonta type, with the capacity of 20 kg/hour, owned by the Chankuap Foundation located in the city of Macas - Morona Santiago. This type of machine consists of an endless screw in to a jacket, through which the product flows while raises its pressure, at the end of the route, it is extruded through a nozzle with a reduced diameter output, the generated pressure cause the oil to be released just before the expulsion of dry waste. The parameters used in the redesign are, power geared motor (5 HP), geared motor rpm (60 rpm); and Sacha inchi's oil extraction parameters as pressure (192.72bar) and temperature (65 ° C). The geometries of the redesigned parts are consider from such machines. The methodology on which we rely for the development of this project was the experimental, which is a systematic process and a scientific approach to research, where the researcher manipulates one or more variables, monitors and measures any changes in other variables. And the scientific method, consisting in systematic observation, measurement, experimentation, development, analysis and modification of hypotheses initially proposed.